2008
DOI: 10.1039/b800954f
|View full text |Cite
|
Sign up to set email alerts
|

The structure and spectra of organic peroxy radicals

Abstract: Recent spectroscopic and computational work on organic peroxy radicals, RO(2), is reviewed and extended with an emphasis on radicals where R is an alkyl group. Detailed experimental spectral, structural relationships are developed and show the dependence of spectral properties on the number of carbon atoms in the radical, and its isomeric and conformeric structure. These empirical relationships are explored and rationalized with the help of a series of quantum chemistry calculations, which are in turn benchmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 86 publications
(151 reference statements)
5
67
0
Order By: Relevance
“…The latter set of calculation has been chosen since it has been shown that, in the case of the alkyl peroxy radicals, the G2 composite method yields very accurate T 00 values. 20 Hence, the optimized geometry from the G2 method, which is MP2͑FULL͒/6-31g͑d͒, 48 ought to be fairly representative of the electronic eigenenergies and corresponding geometries of the molecule, which are necessary for calculations of, respectively, the T 00 values and rotational constants. The final method used was the coupled cluster singlet and doublet, CCSD ͓6-31g͑d͔͒.…”
Section: Electronic Structure Calculations and Molecular Parametmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter set of calculation has been chosen since it has been shown that, in the case of the alkyl peroxy radicals, the G2 composite method yields very accurate T 00 values. 20 Hence, the optimized geometry from the G2 method, which is MP2͑FULL͒/6-31g͑d͒, 48 ought to be fairly representative of the electronic eigenenergies and corresponding geometries of the molecule, which are necessary for calculations of, respectively, the T 00 values and rotational constants. The final method used was the coupled cluster singlet and doublet, CCSD ͓6-31g͑d͔͒.…”
Section: Electronic Structure Calculations and Molecular Parametmentioning
confidence: 99%
“…We demonstrated the suitability of the NIR transition as a species specific, as well as an isomer and even conformer specific, diagnostic technique. 20 However, congestion due to the population of many rotational levels as well as overlap of conformers at room temperature prevents the extraction of spectroscopic parameters, such as rotational and spin-rotational constants, which are highly useful for benchmarking calculations. Other groups have used low to moderate resolution laser sources to study gas-phase methyl and ethyl peroxy by a variety of techniques, including negative-ion photoelectron spectroscopy, 21 photoionization, 22 cw-CRDS in the NIR, 23 and NIR absorption detected by time-of-flight mass spectroscopy, 24 but have similarly failed to obtain, with high precision, molecular parameters, characterizing the rotational and spin-rotational structure.…”
Section: Introductionmentioning
confidence: 99%
“…Peaks E 0 and E exhibit contours similar to those of the G 1 0 G 2 G 3 and G 1 G 2 G 3 band origins, respectively; these features are also blue-shifted by ∼900 cm -1 relative to their respective electronic origins and appear with ∼30% of the intensity, all characteristics typical of O-O stretch progressions. 44 For both conformers, the O-O stretching motion in theà state is spread over two normal modes, ω 16 and ω 15 , with the intensity shared nearly evenly between the two modes for G 1 0 G 2 G 3 and ω 15 being the more active for G 1 G 2 G 3 . This O-O stretch band identification further confirms the empirical assignment of the spectrum to β-HEP.…”
mentioning
confidence: 98%
“…24 On the other hand, although theà −X transition is weak compared to theB −X, theà state is bound and thus the transition presents sharp vibrational and rotational structure. 25 It is therefore a better alternative to probe especially in a mixture.…”
mentioning
confidence: 99%